Association between immune-related adverse events and the prognosis of patients with gastric cancer treated with nivolumab: a meta-analysis - Tian, Qian-Yu; Wang, Cai-E. (Frontiers in Oncology, 2024)
BackgroundNivolumab is an effective treatment option for advanced gastric cancer (GC). This study aimed to conduct a systematic review of existing literature to investigate the relationship between immune-related adverse events (irAEs) and the prognosis of patients with GC treated with nivolumab.MethodsWe comprehensively searched four online literature databases: the Cochrane Central Register of Controlled Trials, PubMed, Embase, Web of Science, until 27 March 2024. The outcome measures of interest included: overall survival (OS), progression-free survival (PFS), hazard ratio (HR), median survival ratio (MSR), objective response rate (ORR), and disease control rate (DCR).ResultsA total of six studies, including 393 patients, met the eligibility criteria. The OS (pooled hazard ratio [HR] = 0.4, 95% confidence interval [CI]: 0.3–0.6, p < 0.05) and PFS (pooled HR = 0.5, 95% CI: 0.4–0.6, p < 0.05) of patients with irAEs were significantly superior to individuals without irAEs. The MSR for OS and PFS were 2.5 (95% CI: 1.5-4.1, p < 0.05) and 2.8 (95% CI: 1.9–4.1, p < 0.05), respectively. Regarding the ORR and DCR, we found that the development of irAEs was significantly associated with higher rates: patients with irAEs had an ORR of 24.7% compared to 6.4% in those without irAEs (risk ratio [RR] = 2.6, p < 0.05), and a DCR of 86.0% compared to 30.3% in those without irAEs (RR = 3.2, p < 0.05).ConclusionThere appears to be a significant correlation between the development of irAEs and the better survival benefits with nivolumab in patients with GC.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022341396.